Fluorine-free casting powder for large round billet high-carbon sulfur-containing steel and application of fluoride-free casting powder

By designing the composition and structure of fluorine-free protective slag, the problems of longitudinal cracks, water port erosion and uneven amount of second cold water in casting of high-carbon sulfur-containing steel in large round billets are solved, and the surface quality and environmental protection effect of the cast billets are improved.

CN119114880APending Publication Date: 2024-12-13XIXIA LONGCHENG METALLURGICAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411253973.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The large round billet high-carbon sulfur-containing steel has longitudinal cracking problems during the casting process, the water outlet erosion speed is fast, resulting in uneven cold water, affecting the surface quality of the casting billet and causing environmental pollution.

Method used

Develop a fluorine-free protective slag containing CaO, SiO2, MgO, Al2O3, Na2O, BaO, MnO, B2O3 and C, design a higher viscosity and melting temperature, reduce the melting point through Na2O, MgO, BaO, and increase the saturation of Al2O3 Concentration improves the stability of absorbed inclusions, and uses MgO, BaO and B2O3 to improve the thickness of the slag film and heat transfer effect.

Benefits of technology

It effectively reduces the incidence of longitudinal cracks, reduces water port erosion, maintains the uniform amount of cold water, improves the surface quality of the casting billet, reduces environmental pollution, and ensures the production of the casting billet and the surface quality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides fluoride-free casting powder for large round billet high-carbon sulfur-containing steel and application of the fluoride-free casting powder, and relates to the technical field of casting powder, the casting powder is prepared from, by mass, 17-23% of CaO, 30-36% of SiO2, 5-7.5% of MgO, 5-10% of Al2O3, 3-7% of Na2O, 5-8% of Ba0, 2-5% of MnO, 0.5-1% of B2O3, 10-15% of C, 0.5-1% of Fe2O3 and the balance inevitable impurities, main raw materials do not contain fluorine, and the casting powder is prepared from, by mass, 20-30% of CaO, 30-36% of SiO2, 5-7.5% of MgO, 5-10% of Al2O3, 3-7% of Na2O, 5-8% of Ba0, the method has the advantages that water gap corrosion is slow, cooling water quality change, secondary cooling water nozzle corrosion and other casting machine equipment cannot be caused, secondary cooling water quantity nonuniformity, influence on casting blank surface quality and environmental pollution cannot be easily caused, and smooth production of large round billet high-carbon sulfur-containing steel casting and casting blank surface quality can be effectively met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective slag, and in particular to a fluorine-free protective slag for large round billet high-carbon sulfur-containing steel and application thereof. Background Art

[0002] At present, due to the serious overcapacity of domestic steel production, the profit of ordinary carbon steel is meager. In order to increase the profit margin, major steel mills have invested in the production of special steels, and round billet high-carbon sulfur steel is one of the products with large current demand and considerable profits. On the one hand, in order to improve the machinability of steel, high S components are added to the steel, but the high-temperature plasticity of the steel is poor, which is easy to cause P and S segregation, the primary ring shell solidification shrinkage is small, the strength is low, the ring shell and the crystallizer are in close contact under the static pressure of the molten steel, the friction force of the billet shell is large during the billet drawing process, and the billet shell is easy to bond with the wall of the crystallizer, resulting in bonding and leakage of steel; on the other hand, the liquidus temperature of this steel is low, the pouring temperature and pouring speed are low, the solidification speed is slow, the thermal strength is poor, the crack sensitivity is large, and it is easy to produce surface cracks. At the same time, the casting section is a round billet, and there is no support point on the surface, so the crack problem is more prominent. When casting large round billet high carbon (carbon content 0.5-0.6%) sulfur-containing steel using the current conventional round billet high carbon protective slag, there are a lot of surface longitudinal cracks and fine longitudinal cracks. At the same time, the conventional protective slag corrodes the nozzle quickly during use, making the cooling water acidic, corroding the secondary cooling water nozzle and other casting machine equipment, causing uneven secondary cooling water, affecting the surface quality of the billet and causing environmental pollution, affecting the smooth casting. In order to solve the current problems in the casting of large round billet high carbon sulfur-containing steel, it is urgent to develop a special protective slag. Summary of the invention

[0003] One of the purposes of the present invention is to provide a fluorine-free protective slag for large round billets of high-carbon sulfur-containing steel, so as to at least solve the technical problems in the prior art of continuous casting of large round billets of high-carbon sulfur-containing steel, such as prominent longitudinal cracking, rapid nozzle erosion, and uneven secondary cooling water volume, which affect the surface quality of the billet and cause environmental pollution.

[0004] The second object of the present invention is to provide a fluorine-free protective slag for large round billet high-carbon sulfur-containing steel and its application in the continuous casting of high-carbon sulfur-containing steel.

[0005] In the first aspect, the present invention provides a fluorine-free protective slag for large round billets of high-carbon sulfur-containing steel, wherein the protective slag comprises the following chemical components in mass percentage (wt%): 17-23% CaO, 30-36% SiO2, 5-7.5% MgO, 5-10% Al2O3, 3-7% Na2O, 5-8% Ba0, 2-5% MnO, 0.5-1% B2O3, 10-15% C and 0.5-1% Fe2O3, and the remainder is unavoidable impurities.

[0006] Furthermore, the protective slag includes the following chemical components in mass percentage (wt%): 17-20% CaO, 32-35% SiO2, 6-7% MgO, 6-9% Al2O3, 3-5% Na2O, 7-8% Ba0, 2-3% MnO, 0.5-1% B2O3, 11-14% C and 0.5-1% Fe2O3, and the remainder is inevitable impurities.

[0007] Furthermore, the raw materials of the protective slag include, by weight percentage, 14-24% glass powder, 2-5% white alkali, 1-2% imported carbon black, 1-2% domestic carbon black, 10-20% medium carbon graphite, 30-40% wollastonite, 3-6% manganese carbonate, 5-8% magnesia, 7-9% bauxite, 1-2% borax, 10-14% barium carbonate, and 1.5-2% binder.

[0008] Furthermore, the raw materials of the protective slag include, by weight percentage, 15-20.1% of glass powder, 3-4% of white alkali, 1-1.5% of imported carbon black, 1-1.5% of domestic carbon black, 11-13% of medium carbon graphite, 30-32% of wollastonite, 4-5% of manganese carbonate, 6.7-7.5% of magnesia, 7-8% of bauxite, 1-2% of borax, 10-12% of barium carbonate, and 1.5-2% of binder.

[0009] Furthermore, the carbon content of the imported carbon black is greater than 98%, the oil absorption value is greater than 100 g / cm3, and the iodine absorption value is greater than 130 g / kg;

[0010] Preferably, the carbon content of the domestic carbon black is greater than 98%, the oil absorption value is greater than 35 g / cm3, and the iodine absorption value is greater than 55 g / kg.

[0011] Furthermore, the binder includes dextrin or sodium carboxymethyl cellulose, preferably dextrin.

[0012] Furthermore, the binary basicity of the protective slag is 0.5 to 0.6.

[0013] Furthermore, the melting temperature of the mold slag is 1150-1180°C.

[0014] Furthermore, the viscosity of the mold slag at 1300° C. is 1.3-1.5 Pa·s.

[0015] In a second aspect, the present invention provides the use of the fluorine-free protective slag for large round billet high-carbon sulfur-containing steel according to any one of the aforementioned embodiments in the continuous casting of high-carbon sulfur-containing steel;

[0016] Preferably, the cross section of the high carbon sulfur-containing steel continuous casting ingot is φ550-700 mm;

[0017] Preferably, the casting speed of the high carbon sulfur-containing steel continuous casting is 0.2-0.5 m / min.

[0018] The present invention provides a fluorine-free protective slag for large round billet high-carbon sulfur-containing steel. The main raw materials of the protective slag do not contain fluorine, and the erosion to the water inlet is slow, which will not cause the change of cooling water quality and the erosion to the secondary cooling water nozzle and other casting machine equipment. At the same time, it is not easy to cause uneven secondary cooling water, affect the surface quality of the billet and cause environmental pollution, and can effectively meet the production of large round billet high-carbon sulfur-containing steel casting and the surface quality of the billet. In order to replace the role of F-, Na2O, MgO, MnO, B2O3 and BaO are used in the protective slag to reduce the melting point of the protective slag. The addition of appropriate amounts of B2O3 and BaO can both increase the saturation concentration of Al2O3 in the protective slag and improve the stability of the protective slag after absorbing inclusions. The presence of BaO can promote the increase of low-melting silicate glass phase, hinder the crystallization of liquid slag, improve the lubrication of slag, improve the surface quality of the billet, and reduce the occurrence of cracks. B2O3 and BaO both have the effect of reducing the melting point of protective slag, and have a positive effect on absorbing impurities such as Al2O3. When the sulfur content of molten steel increases, the surface tension of molten steel becomes smaller. It is necessary to increase the surface tension of protective slag and increase the interfacial tension of slag to avoid the generation of slag rolls during design. MgO and BaO cations have large electrostatic potential, so it is preferred to use MgO and BaO materials at the same time in a large proportion. B2O3 cations have small electrostatic potential, so the proportion of use is reduced. Protective slag has a higher viscosity, and the increase in viscosity is conducive to the increase in slag film thickness. In addition, the colored MnO has an obstructive effect on heat transfer, so that the lubrication and heat transfer between the continuous casting shell and the crystallizer are guaranteed at the same time, and the continuous casting defects are naturally reduced. The existing technology solves the problems of prominent longitudinal cracks in the continuous casting of large round billets with high carbon sulfur-containing steel, fast water inlet erosion speed, and uneven secondary cooling water, which affects the surface quality of the casting billet and causes environmental pollution.

[0019] On the other hand, the above-mentioned fluorine-free protective slag for large round billet high-carbon sulfur-containing steel is used in the continuous casting of high-carbon sulfur-containing steel, which is applied to the continuous casting of high-carbon sulfur-containing steel with a cross-section of φ550-700mm and a pulling speed of 0.2-0.5m / min. The slag film is mainly in a glassy state, which can provide good lubrication and heat transfer effects, and can effectively reduce the probability of sticking alarms and steel leakage accidents during the continuous casting process, and reduce cracks on the surface of the ingot. DETAILED DESCRIPTION

[0020] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0021] The methods and techniques of the present invention are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.

[0022] On the one hand, the present invention provides a fluorine-free protective slag for large round billets of high-carbon sulfur-containing steel, wherein the protective slag comprises the following chemical components in mass percentage (wt%): 17-23% CaO, 30-36% SiO2, 5-7.5% MgO, 5-10% Al2O3, 3-7% Na2O, 5-8% Ba0, 2-5% MnO, 0.5-1% B2O3, 10-15% C and 0.5-1% Fe2O3, and the remainder is unavoidable impurities.

[0023] The main raw materials of the protective slag do not contain fluorine, and the erosion of the water nozzle is slow, which will not cause changes in the cooling water quality and erosion of the secondary cooling water nozzle and other casting machine equipment. At the same time, it is not easy to cause uneven secondary cooling water, affect the surface quality of the ingot and cause environmental pollution. It can effectively meet the production of large round billets and high-carbon sulfur-containing steel casting and the surface quality of the ingot. In addition, considering that the shell surface of the round billet has no support points, it is easy to crack relative to the square billet or slab. When the sulfur content is high, it is more likely to crack. Therefore, the protective slag needs to have a higher viscosity to increase the thickness of the slag film and improve the crack control ability. Therefore, in the design of the composition, in order to replace the role of F-, Na2O, MgO, MnO, B2O3 and BaO are used in the protective slag to reduce the melting point of the protective slag, and an appropriate amount of B2O3 and BaO are added. Both can increase the saturation concentration of Al2O3 in the protective slag and improve the stability of the protective slag after absorbing inclusions. The presence of BaO can promote the increase of low-melting silicate glass phase, hinder the crystallization of liquid slag, improve the lubrication of molten slag, improve the surface quality of ingot, and reduce the occurrence of cracks. Both B2O3 and BaO have the effect of reducing the melting point of protective slag, and have a positive effect on absorbing impurities such as Al2O3. After the sulfur content of molten steel increases, the surface tension of molten steel becomes smaller. It is necessary to increase the surface tension of protective slag during design, increase the interfacial tension of slag, and avoid the generation of slag rolls. MgO and BaO cations have large electrostatic potential, and it is preferred to use MgO and BaO materials at the same time in a large proportion. B2O3 cations have small electrostatic potential, and the proportion of use is reduced. Protective slag has a higher viscosity, and the increase in viscosity is conducive to the increase in slag film thickness. In addition, the colored MnO has an obstructive effect on heat transfer, so that the lubrication and heat transfer between the continuous casting shell and the crystallizer are guaranteed at the same time, and the continuous casting defects are naturally reduced. The technical problems of prominent longitudinal cracking problems, fast water inlet erosion speed, and uneven secondary cooling water volume in the existing technology of large round billet high-carbon sulfur-containing steel continuous casting, affecting the surface quality of the ingot and causing environmental pollution are solved.

[0024] The mass percentage of CaO may be, but is not limited to, 17%, 18%, 19%, 20%, 21%, 22% or 23%, or any percentage between 17 and 23%.

[0025] The mass percentage of the SiO2 may be, but is not limited to, 30%, 31%, 32%, 33%, 34%, 35% or 36%, or any percentage between 30 and 36%.

[0026] The mass percentage of MgO may be, but is not limited to, 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2% or 7.5%, or any percentage between 5 and 7.5%.

[0027] The mass percentage of the Al2O3 may be, but is not limited to, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, or any percentage between 5 and 10%.

[0028] The mass percentage of the Na2O may be, but is not limited to, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%, or any percentage between 3 and 7%.

[0029] The mass percentage of Ba0 may be, but is not limited to, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, or any percentage between 5 and 8%.

[0030] The mass percentage of MnO may be, but is not limited to, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, or any percentage between 2% and 5%.

[0031] The mass percentage of B2O3 may be, but is not limited to, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, or any percentage between 0.5 and 1%.

[0032] The mass percentage of C may be, but is not limited to, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5% or 15%, or any percentage between 10 and 15%.

[0033] The mass percentage of the Fe2O3 may be, but is not limited to, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, or any percentage between 0.5 and 1%.

[0034] In some specific embodiments, the protective slag includes the following chemical components in mass percentage (wt%): 17-20% CaO, 32-35% SiO2, 6-7% MgO, 6-9% Al2O3, 3-5% Na2O, 7-8% Ba0, 2-3% MnO, 0.5-1% B2O3, 11-14% C and 0.5-1% Fe2O3, and the remainder is unavoidable impurities.

[0035] In some specific embodiments, the raw materials of the protective slag include, by weight percentage, 14-24% glass powder, 2-5% white alkali, 1-2% imported carbon black, 1-2% domestic carbon black, 10-20% medium carbon graphite, 30-40% wollastonite, 3-6% manganese carbonate, 5-8% magnesia, 7-9% bauxite, 1-2% borax, 10-14% barium carbonate, and 1.5-2% binder.

[0036] Among them, the use of different carbon blacks and medium carbon graphites is beneficial to the uniformity and stability of slag melting, making the liquid slag layer more stable and the smooth continuous casting easier to ensure.

[0037] In some specific embodiments, the raw materials of the protective slag include, by weight percentage, 15-20.1% glass powder, 3-4% white alkali, 1-1.5% imported carbon black, 1-1.5% domestic carbon black, 11-13% medium carbon graphite, 30-32% wollastonite, 4-5% manganese carbonate, 6.7-7.5% magnesia, 7-8% bauxite, 1-2% borax, 10-12% barium carbonate, and 1.5-2% binder.

[0038] In some specific embodiments, the carbon content of the imported carbon black is greater than 98%, and the oil absorption value is greater than 100 g / cm 3 , iodine absorption value>130g / kg;

[0039] In some specific embodiments, the carbon content of the domestic carbon black is greater than 98%, and the oil absorption value is greater than 35 g / cm 3 , iodine absorption value>55g / kg.

[0040] In some specific embodiments, the binder includes dextrin or sodium carboxymethyl cellulose, preferably dextrin.

[0041] In terms of index design, given the characteristics of steel grades, priority is given to reducing friction, which requires the mold slag to form a good glassy slag film, so a lower basicity is designed; the inventors have determined that the basicity of the mold slag is more suitable at 0.5-0.6 through a large number of creative experiments without fluorine. In some specific embodiments, the binary basicity of the mold slag is 0.5-0.6. Under this basicity condition, the mold slag has excellent lubricity.

[0042] In some specific embodiments, the melting temperature of the mold slag is 1150-1180°C.

[0043] At the same time, it has a higher viscosity, which increases the overall thickness of the slag film, better controls the heat transfer rate, and ensures the quality of the casting and the smoothness of continuous casting. In some specific embodiments, the viscosity of the mold slag at 1300°C is 1.3-1.5 Pa·s.

[0044] The above-mentioned fluorine-free protective slag for large round billet high-carbon sulfur-containing steel forms suitable liquid slag during the casting process of large round billet high-carbon sulfur-containing steel. The slag film is mainly in a glassy state, which can provide good lubrication and heat transfer effects and reduce the occurrence of longitudinal cracks in the casting billet.

[0045] According to another aspect of the present invention, there is also provided the use of the above-mentioned fluorine-free protective slag for large round billet high-carbon sulfur-containing steel in the continuous casting of high-carbon sulfur-containing steel;

[0046] The cross section of the high-carbon sulfur-containing steel continuous casting ingot is φ550-700 mm, and the pulling speed is 0.2-0.5 m / min.

[0047] It is used for continuous casting of high-carbon sulfur-containing steel with a cross-section of φ550-700mm and a casting speed of 0.2-0.5m / min. The slag film is mainly in a glassy state, which can provide good lubrication and heat transfer effects, and can effectively reduce the probability of adhesion alarms and steel leakage accidents during continuous casting, and reduce surface cracks on the ingot. At the same time, the protective slag does not contain fluorine, and slowly corrodes the water inlet, and will not cause changes in the cooling water quality and erode the secondary cooling water nozzle and other casting machine equipment. At the same time, it is not easy to cause uneven secondary cooling water volume, affect the surface quality of the ingot and cause environmental pollution, and can effectively meet the production conditions and surface quality of large round billet high-carbon sulfur-containing steel casting.

[0048] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] Example 1

[0050] A fluorine-free protective slag for large round billet high-carbon sulfur-containing steel, the raw materials of which are composed of the following substances in weight percentage: 15% glass powder, 4% caustic soda, 1.5% imported carbon black, 1.0% domestic carbon black, 13% medium carbon graphite, 31.3% wollastonite, 4% manganese carbonate, 7.5% magnesia, 8% bauxite, 1.7% borax, 11.0% barium carbonate, 2% dextrin. The protective slag contains 18.80% CaO, 32.12% SiO2, 6.76% MgO, 6.78% Al2O3, 4.59% Na2O, 7.50% Ba0, 2.26% MnO, 0.64% B2O3, 13.02% C, 0.88% Fe2O3, and the balance is inevitable impurities.

[0051] The binary basicity (CaO / SiO2) of the above-mentioned protective slag is 0.59, the melting temperature is 1163°C, and the viscosity is 1.33 Pa·s at 1300°C.

[0052] The obtained large round billet high carbon sulfur-containing steel was tested in a steel plant with fluorine-free protective slag. The test slag model was XLG-1, the test steel type was Y55CrNiMnMoVS (SM1), the cross section was 600mm round billet, and the pulling speed was 0.25m / min. A total of 2T of protective slag was tested. During the test, the protective slag had good spreadability and fluidity in the crystallizer, the thickness of the liquid slag layer was 8-10mm, the three-layer structure was obvious, the thickness of the liquid slag layer was appropriate, the size of the crystallizer liquid surface flame was normal, the average slag consumption was 0.35kg / T, the slag strips in the crystallizer were generated slowly, and the slag strips were picked up once every 4 furnaces on average. No obvious slag pits and cracks were found on the surface of the ingot produced in the test, and the test effect was good.

[0053] Example 2

[0054] A fluorine-free protective slag for high-carbon sulfur-containing steel in large round billets, the raw materials of which are composed of the following substances in weight percentage: 20.1% glass powder, 3.1% caustic soda, 1.0% imported carbon black, 1.0% domestic carbon black, 11.3% medium carbon graphite, 30.5% wollastonite, 5% manganese carbonate, 7.8% magnesia, 7% bauxite, 1.4% borax, 10.3% barium carbonate, 1.5% dextrin. The chemical composition of the protective slag contains 17.95% CaO, 34.76% SiO2, 0.71% Fe2O3, 6.24% Al2O3, 4.78% Na2O, 2.82% MnO, 7.0% Ba0, 7.0% MgO, 0.54% B2O3, 12.46% C, and the balance is inevitable impurities.

[0055] The binary basicity (CaO / SiO2) of the above-mentioned protective slag is 0.52, the melting temperature is 1152°C, and the viscosity is 1.46 Pa·s at 1300°C.

[0056] The obtained large round billet high carbon sulfur steel was tested in a steel plant with fluorine-free protective slag. The test slag model was XLG-2, the test steel type was Y55CrNiMnMoVS (SM1), the cross-section was 700mm round billet, and the pulling speed was 0.20m / min. A total of 1T of protective slag was tested. During the test, the protective slag had good spreadability and fluidity in the crystallizer, the thickness of the liquid slag layer was about 10mm, the size of the crystallizer liquid surface flame was normal, the average slag consumption was 0.33kg / T, the glassy proportion of the slag film sample taken after stopping pouring was high, and the proportion of fine cracks was significantly reduced after the third furnace casting billet was shot blasted off the line.

[0057] Example 3

[0058] A fluorine-free protective slag for large round billet high-carbon sulfur-containing steel, the raw materials of which are composed of the following materials in percentage by weight: 16.9% glass powder, 3.9% caustic soda, 1% imported carbon black, 1.5% domestic carbon black, 11.5% medium carbon graphite, 30.84% ​​wollastonite, 5% manganese carbonate, 6.7% magnesia, 11.8% barium carbonate, 7.2% bauxite, 1.34% borax, 2% sodium carboxymethyl cellulose. The protective slag contains 18.59% CaO, 32.82% SiO2, 0.68% Fe2O3, 6.34% Al2O3, 4.48% Na2O, 2.82% MnO, 8.0% BaO, 6.0% MgO, 0.51% B2O3 and 12.12% C, and the balance is inevitable impurities.

[0059] The binary basicity (CaO / SiO2) of the above-mentioned protective slag is 0.57, the melting temperature is 1175°C, and the viscosity is 1.40 Pa·s at 1300°C.

[0060] The obtained large round billet high carbon sulfur steel was tested in a steel plant with fluorine-free protective slag. The test slag model was XLG-3, the test steel grade was Y55CrNiMnMoVS (SM1) -1, the cross-section was 550mm round billet, and the pulling speed was 0.32m / min. A total of 1T of protective slag was tested. During the test, the protective slag had good spreadability and fluidity in the crystallizer, the thickness of the liquid slag layer was 8-10mm, the size of the crystallizer liquid surface flame was normal, the average slag consumption was 0.34kg / T, the glassy proportion of the slag film sample taken after stopping pouring was high, and the proportion of fine cracks was significantly reduced after the fourth furnace casting billet was shot blasted off the line.

[0061] The fluorine-free continuous casting crystallizer protective slag for high-carbon sulfur-containing steel provided in Examples 1-3 can adapt to production conditions of different cross-sections (φ550~700mm), and the produced ingots do not have obvious surface quality defects such as depressions and cracks. The ratio of surface fine cracks is also reduced from 15% to 7%, which can effectively solve the surface quality problem of the ingots. The fluorine detected in the circulating water is extremely small, with a content of only 0.6mg / L, which may be related to the early use of fluorine-containing protective slag remaining in the environment.

[0062] Comparative Example 1

[0063] This comparative example uses a fluorine-containing protective slag specially used for high-carbon sulfur-containing steel of conventional large round billets, and its raw materials are composed of the following substances: 16% glass powder, 13% fluorite, 2.9% white soda, 1% imported carbon black, 1.9% domestic carbon black, 10.8% medium carbon graphite, 31% wollastonite, 4% manganese carbonate, 1.4% magnesia, 1.5% bauxite, 2% borax, 12.5% ​​carbon-free soot, and 2% dextrin. The chemical composition of the protective slag contains 26.32% CaO, 37.30% SiO2, 1.13% Fe2O3, 5.11% Al2O3, 2.71% Na2O, 2.26% MnO, 5.20% F - , 2.29% MgO, 1.44% B2O3 and 10.26% C, and the balance are inevitable impurities.

[0064] The binary basicity (CaO / SiO2) of the above-mentioned protective slag is 0.67, the melting temperature is 1167°C, and the viscosity is 1.32 Pa·s at 1300°C.

[0065] The mold slag obtained in this comparative example was tested according to the method of Example 1, and the results showed that the liquid slag layer was 5-8mm, and the consumption was 0.45Kg / T, which was normal. Because the chemical composition of this comparative example was the original conventional fluorine-containing mold slag, the steel plant sampled and tested the secondary cooling circulating water during its use and found that the fluorine content was 18.7mg / L. The secondary cooling water nozzle erosion problem always existed, resulting in unstable water volume, uneven heating of the ingot surface, and small crack defects.

[0066] Comparative Example 2

[0067] Compared with Example 1, the raw materials of the fluorine-free protective slag for high-carbon sulfur-containing steel for large round billets provided in this comparative example are specifically composed of the following substances: 14% glass powder, 12% white alkali, 1% imported carbon black, 1% domestic carbon black, 13.5% medium carbon graphite, 36% wollastonite, 4% manganese carbonate, 2% magnesia, 5% barium carbonate, 6% bauxite, 4.0% borax, and 1.5% dextrin. The chemical composition of the protective slag contains 18.29% CaO, 32.16% SiO2, 0.79% Fe2O3, 5.44% Al2O3, 7.76% Na2O, 2.26% MnO, 3.80% Ba0, 2.73% MgO, 1.63% B2O3, 14.97% C, and the balance is unavoidable impurities.

[0068] The binary basicity (CaO / SiO2) of the above-mentioned protective slag is 0.56, the melting temperature is 1100°C, and the viscosity is 1.28 Pa·s at 1300°C.

[0069] The high-carbon sulfur-containing steel special fluorine-free continuous casting crystallizer protective slag obtained in this comparative example was tested according to the method of Example 1, and the results showed that: in this comparative example, due to the increase in the amount of caustic soda and borax, the decrease in the amount of barium carbonate and magnesia, the melting temperature and viscosity of the protective slag decreased. During the use of the protective slag in the crystallizer, the thickness of the liquid slag layer was 5-7mm, the liquid slag layer was thin, the consumption was 0.55kg / t, the consumption was large, the slag film heat transfer was fast, the crystallizer expert system showed a heat flux of 2.5MW / m2, the heat flux was high, and longitudinal crack defects were easily generated under non-steady state (speeding up pouring and changing water outlets, etc.), and the longitudinal cracks accounted for 8%.

[0070] Comparative Example 3

[0071] Compared with Example 1, the raw materials of the fluorine-free protective slag for high-carbon sulfur-containing steel for large round billets provided in this comparative example are composed of the following substances: 8% cement clinker, 12% white alkali, 1% imported carbon black, 1% domestic carbon black, 14.3% medium carbon graphite, 33.3% wollastonite, 4% manganese carbonate, 3% magnesia, 5% barium carbonate, 4.4% bauxite, 9.0% borax, and 2.0% dextrin. The chemical composition of the protective slag contains 28.48% CaO, 30.09% SiO2, 0.96% Fe2O3, 3.49% Al2O3, 5.09% Na2O, 2.26% MnO, 3.80% Ba0, 2.79% MgO, 3.43% B2O3 and 13.59% C, and the balance is unavoidable impurities.

[0072] The binary basicity (CaO / SiO2) of the above-mentioned protective slag is 0.95, the melting temperature is 960°C, and the viscosity is 0.79 Pa·s at 1300°C.

[0073] The fluorine-free continuous casting crystallizer protective slag for high-carbon sulfur-containing steel obtained in this comparative example was tested according to the method of Example 1, and the results showed that: since the comparative example had a large amount of caustic soda and an even larger amount of borax, and low contents of barium carbonate, magnesia and manganese carbonate, the melting temperature and viscosity of the protective slag were too low. The protective slag obtained in this comparative example melted quickly in the crystallizer. During use, the thickness of the liquid slag layer was 5 mm, and the consumption of the protective slag was 0.66 kg / t. Due to the low viscosity, the vibration marks were relatively deep under low pulling speeds, and the iron oxide scale was thick. After sampling and pickling, transverse cracks were found at the bottom of the vibration marks.

[0074] To sum up, the fluorine-free continuous casting crystallizer protective slag for large round billets with high carbon and sulfur-containing steel provided in the present application is suitable for the casting of large round billets with high carbon and sulfur-containing steel, which can ensure the smooth operation of the continuous casting process of large round billets with high carbon and sulfur-containing steel, prevent crack defects from appearing on the surface of the billets, and obtain good billet quality. Moreover, through material replacement, the quality of the secondary cooling water is improved, which plays a good role in equipment, billet quality, and environmental protection.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A fluorine-free protective slag for large round billet high-carbon sulfur-containing steel, characterized in that: The protective slag includes the following chemical components in mass percentage (wt%): 17-23% CaO, 30-36% SiO2, 5-7.5% MgO, 5-10% Al2O3, 3-7% Na2O, 5-8% Ba0, 2-5% MnO, 0.5-1% B2O3, 10-15% C and 0.5-1% Fe2O3, and the remainder is inevitable impurities.

2. The fluorine-free protective slag for large round bloom high-carbon sulfur-containing steel according to claim 1, characterized in that: The protective slag includes the following chemical components in mass percentage (wt%): 17-20% CaO, 32-35% SiO2, 6-7% MgO, 6-9% Al2O3, 3-5% Na2O, 7-8% Ba0, 2-3% MnO, 0.5-1% B2O3, 11-14% C and 0.5-1% Fe2O3, and the remainder is inevitable impurities.

3. The fluorine-free protective slag for large round bloom high-carbon sulfur-containing steel according to claim 1, characterized in that: Measured by weight percentage, the raw materials of the protective slag include 14-24% glass powder, 2-5% white alkali, 1-2% imported carbon black, 1-2% domestic carbon black, 10-20% medium carbon graphite, 30-40% wollastonite, 3-6% manganese carbonate, 5-8% magnesia, 7-9% bauxite, 1-2% borax, 10-14% barium carbonate, and 1.5-2% binder.

4. The fluorine-free protective slag for large round bloom high-carbon sulfur-containing steel according to claim 3, characterized in that: Measured by weight percentage, the raw materials of the protective slag include 15-20.1% glass powder, 3-4% white alkali, 1-1.5% imported carbon black, 1-1.5% domestic carbon black, 11-13% medium carbon graphite, 30-32% wollastonite, 4-5% manganese carbonate, 6.7-7.5% magnesia, 7-8% bauxite, 1-2% borax, 10-12% barium carbonate, and 1.5-2% binder.

5. The fluorine-free protective slag for large round bloom high-carbon sulfur-containing steel according to claim 4, characterized in that: The carbon content of the imported carbon black is >98%, and the oil absorption value is >100g / cm 3 , iodine absorption value>130g / kg; Preferably, the carbon content of the domestically produced carbon black is greater than 98%, and the oil absorption value is greater than 35 g / cm 3 , iodine absorption value>55g / kg.

6. The fluorine-free protective slag for large round bloom high-carbon sulfur-containing steel according to claim 4, characterized in that: The binder includes dextrin or sodium carboxymethyl cellulose, preferably dextrin.

7. The fluorine-free mold slag for large round bloom high-carbon sulfur-containing steel according to any one of claims 1 to 6, characterized in that: The binary basicity of the protective slag is 0.5-0.

6.

8. The fluorine-free protective slag for large round bloom high-carbon sulfur-containing steel according to claim 7, characterized in that: The melting temperature of the protective slag is 1150-1180°C.

9. The fluorine-free protective slag for large round bloom high-carbon sulfur-containing steel according to claim 8, characterized in that: The viscosity of the mold slag at 1300° C. is 1.3-1.5 Pa·s.

10. Use of the fluorine-free protective slag for large round billet high-carbon sulfur-containing steel according to any one of claims 1 to 9 in continuous casting of high-carbon sulfur-containing steel; Preferably, the cross section of the high carbon sulfur-containing steel continuous casting is Preferably, the casting speed of the high carbon sulfur-containing steel continuous casting is 0.2-0.5 m / min.